Perceived constraints among adolescent girls in accessing health care in Assam, India - Pralip Kumar Narzary (Universiti Kebangsaan Malaysia, 2012)
Adolescence is a period of transition from childhood to adulthood. The health need of adolescent girls is quite different from other groups of population and has strong policy implications. Study on perceived constraints in accessing health care is quite essential, because it highly affects the future course of action. This study aims to assess the perceived constraints of never married adolescent girls in accessing health care in Assam, India. Methods This study used the National Family Health Survey 2005-06 data which covered 493 never married adolescent girls in Assam. Percentage distribution, median and inter quartile range were assessed, associations were cross tabulated and logistic regression was applied to assess degree of associations using SPSS 15. Results In Assam, the most commonly perceived constraints in accessing health care by never married adolescent girls were the concern about availability of the drugs followed by getting money needed for treatment. About 25.8 percent did not perceive any constraint, whereas 74.2 percent of them perceived some constraints, and about 51.4 percent of the girls perceived between zero-two constraint(s). Bi-variate analyses show that perception greatly varies across different groups or segments. Multi-variate analysis shows that mainly wealth index of the household, native language and education of the girls affected the perception of the never married adolescent girls. Conclusions To remove the perceived constraints, government may manage the entire health care services through which availability, accessibility, affordability, acceptability and quality can be standardized. Further, efforts are also needed to ensure peace and harmony in the state.